HUBUNGAN POLA ASUH PEMBERIAN MAKAN DENGAN KEJADIAN STUNTING - Abdul Syafei; Rahmalia Afriyani; Apriani (Jurnal Kesehatan dan Pembangunan, 2023)
Stunting that fails to be addressed will have an impact on brain development so that the intelligence level of toddlers becomes less. Feeding parenting is the dominant factor causing stunting. Gandus sub-district is the sub-district with the highest number of stunting toddlers in the city of Palembang, namely 140 toddlers. Objective: to determine the effect of feeding parenting with the incidence of stunting under five. Methods: This research is an analytical survey research with a cross-sectional design approach. The research was carried out on July 4th-30th, 2022 and the sample in the study was mothers who had toddlers and visited the posyandu in the working area of ​​the Palembang Gandus Public Health Center with a total of 98 respondents. Results: It was found that only 13 (13.3%) respondents had stunting toddlers, 66 (67.3%) respondents had poor feeding parenting patterns. Furthermore, the results of the chi square test showed that there was a significant relationship between feeding parenting and the incidence of stunting (p value: 0.022). Conclusion: The better the parenting pattern in providing food by a mother, the smaller the chance for her toddler to suffer from stunting. Suggestion: Health education about feeding parenting should be carried out on a scheduled basis to prevent stunting and the need for continuous monitoring of the growth of children with stunting.